2023
DOI: 10.1200/po.22.00211
|View full text |Cite
|
Sign up to set email alerts
|

HRAS Mutations Define a Distinct Subgroup in Head and Neck Squamous Cell Carcinoma

Abstract: PURPOSE In head and neck squamous cell carcinoma (HNSCC), HRAS mutation is a new actionable oncogene driver. We aimed to evaluate HRAS mutational variants, comutation profile, and survival outcomes of this molecularly defined population. METHODS We leveraged four deidentified patient data sets with HRAS-mutant HNSCC, MD Anderson Cancer Center, Kura Oncology, Inc trial, Foundation Medicine, and American Association for Cancer Research GENIE v.12. Patient demographic information and clinical courses were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…HRASmt status was associated with poorer clinical outcomes in HNSCC, and no difference in OS was observed between the different HRAS codon mutations. Similar findings were recently reported for 249 HRASmt HNSCC samples with median diseasefree survival (DFS) of 4.0 months and OS between 15 and 25.5 months [20], which were slightly longer than those observed in our cohort. This confirms the aggressive clinical nature of HRASmt HNSCC, as has been observed previously [37].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…HRASmt status was associated with poorer clinical outcomes in HNSCC, and no difference in OS was observed between the different HRAS codon mutations. Similar findings were recently reported for 249 HRASmt HNSCC samples with median diseasefree survival (DFS) of 4.0 months and OS between 15 and 25.5 months [20], which were slightly longer than those observed in our cohort. This confirms the aggressive clinical nature of HRASmt HNSCC, as has been observed previously [37].…”
Section: Discussionsupporting
confidence: 92%
“…With inhibitors for TP53wt HRASmt UC under development [29], our results provide further evidence for targeting HRASmt UC. Finally, the alterations observed in our HNSCC cohort echo a previously reported dataset in which CASP8, TERT, and NOTCH1 were also frequent co-mutations in HRASmt HNSCC, while CCND1 had higher amplification in HRASwt compared to HRASmt [20] (Figure 2). However, we also report a significantly increased co-occurrence of HRASmt with CTCF and FAT1 mutations (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This widely used method provides a quantitative definition of drug interactions ( CI = 1 additive effect, CI > 1 antagonistic and CI < 1 synergistic effect). We first investigated sotorasib, which is already approved for clinical treatment of KRAS-G12C lung adenocarcinoma, in combination with tipifarnib, an FTi that was recently granted Breakthrough Therapy Designation for treatment of HRAS mutant head and neck squamous cell carcinoma [ 31 ]. To test combinational therapy, we first tested three KRAS-G12C mutant cell lines: H358 a sotorasib sensitive; SW1573, a sotorasib-resistant and a novel patient-derived cell line, PF139.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that in all cohorts, the most common mutation encountered was G12S, which was 25% in MDACC, 30% in Kura, 26% in the FMI data set, and 41% in AACR Project GENIE v.12 cohort, respectively. Other than codon 12 and codon 13, codon 61 was also frequently reported for mutation which was presented as 31% in the MDACC, 11% in Kura, 27% in the FMI data set, and 20% in AACR Project GENIE v.12 cohort [ 29 ].…”
Section: Reviewmentioning
confidence: 99%